Adversity Quotient (AQ) dan Penalaran Kreatif Matematis Mahasiswa Calon Guru - Hidayat, Wahyu; Herdiman, Indri; Aripin, Usman; Yuliani, Anik; Maya, Rippi (Jurnal Elemen, 2018)
This study is experimental research that aims to know and examine in depth about the influence of AQ of pre-service mathematics teacher toward the achievement of mathematical creative reasoning ability. The population of this study is the pre-service mathematics teacher in Cimahi City, West Java, Indonesia; while the sample is 60 pre-service mathematics teachers selected purposively. The instruments of this study are tests and non-tests. They are based on the assessment of good characteristics towards students mathematical creative reasoning abilities, while the non-test instrument is based on the assessment of good characteristics towards AQ. The results of this research show that: (1) AQ gives positive influence to the development of mathematical creative reasoning ability of pre-service mathematics teacher with the influence of 60.9%, while the rest of it (39.1%) is influenced by other factors outside AQ; (2) The mathematical creative reasoning ability of the prospective teacher students is more develop in AQ Climber type, whereas students who have Camper and Quitter AQ types still tend to have thinking patterns in solving problems with imitative reasoning; (3) Students belonging to the Quitter AQ type still tend to have errors related to the idea of solving problems and mathematical expressions.